Organizational Justice and Organizational Citizenship Behavior (OCB): A Systematic Literature Review - Ardhiana Naufa Rendha Oktaviani; Meita Santi Budiani (Al-Qalam Institue, 2026)
This study aims to examine organizational justice as a predictor of Organizational Citizenship Behavior (OCB) through a systematic synthesis of empirical evidence and to explain the relationship using Social Exchange Theory. The study focuses on how fairness perceptions influence employees’ voluntary behaviors and the psychological mechanisms underlying this relationship. This research employs a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines to ensure methodological rigor and transparency. Data were collected from the Scopus database using keywords related to organizational justice and OCB. From 215 identified articles, 14 empirical studies met the inclusion criteria and were analyzed. The results indicate that organizational justice consistently has a positive and significant effect on OCB across various organizational contexts. Employees who perceive distributive, procedural, and interactional justice are more likely to engage in extra-role behaviors such as helping colleagues and voluntarily contributing to organizational effectiveness. The relationship is strengthened by mediating factors such as job satisfaction, organizational commitment, and psychological ownership. Additionally, organizational justice reduces negative outcomes such as burnout and turnover intention. These findings support Social Exchange Theory, which explains that fair treatment encourages reciprocal positive employee behavior. The study implies that organizations should prioritize fairness in decision-making, reward distribution, and interpersonal treatment to enhance employee citizenship behavior and overall organizational effectiveness.